Penerapan Konsep Perancangan Terpadu (Integrated Design) untuk Mewujudkan Bangunan Hemat Energi - Pebriyanti, Ni Luh Putu Eka (Jurnal Arsitektur Universitas Udayana, 2025)
Energy conservation is an effort to reduce energy waste so as to produce efficiency in its use. In this case, a building is one that requires energy consumption in managing the building. Energy efficient building are one approach that can improve building performance so that it is more optimal and provides comfort for users. The concept of integrated design is solution that can be implemented which also includes aspects of sustainable design to reduce negative impacts on the surrounding environment and can create comfort and health for residents. This research was conducted with the aim of providing problem solving related to the issue of saving energy use in the Advance Research Laboratory building that located at the Faculty of Engineering, Udayana University, Badung-Bali. The phenomenom that occurs is that the building’s performance is not optimal in accommodating teaching and learning activities after occupied for a periode of time and there is a waste of energy. The research method used is a qualitative method where an assessment is carried out on existing buildings based on architectural design aspects and building system aspects. The resulting output is the strategies pursued through implementation of the Integrated Design Concept capable to reduce excessive energy consumption in the construction of the Advance Research Laboratory Buiding. Keywords: energy efficient building, building performance, integrated design concept